Cardiovascular event‐free survival after adjuvant radiation therapy in breast cancer patients stratified by cardiovascular risk. (10th July 2014) - Onwudiwe, Nneka C.; Kwok, Young; Onukwugha, Eberechukwu; Sorkin, John D.; Zuckerman, Ilene H.; Shaya, Fadia T.; Daniel Mullins, C.
Abstract The objective of this study was to estimate the risk of a cardiovascular event or death associated with modern radiation in a population of elderly female breast cancer patients with varying baseline cardiovascular risk. The data used for this analysis are from the linked Surveillance, Epidemiology, and End‐Results (SEER)‐Medicare database. The retrospective cohort study included women aged 66 years and older with stage 0–III breast cancer diagnosed between 2000 and 2005. Women were grouped as low, intermediate, or high cardiovascular risk based on the presence of certain clinical diagnoses. The risk for the combined outcome of a hospitalization for a cardiovascular event or death within 6 months and 24 months of diagnosis was estimated using a multivariable Cox model. The median follow‐up time was 24 months. Among the 91, 612 women with American Joint Committee on Cancer (AJCC) stage 0–III breast cancer: 39, 555 (43.2%) were treated with radiation therapy and 52, 057 (56.8%) were not. The receipt of radiation therapy in the first 6 months was associated with a statistically significant increased risk for the combined outcome in women categorized as high risk (HR = 1.510; 95% CI, 1.396–1.634) or intermediate risk (HR = 1.415; 95% CI, 1.188–1.686) but not low risk (HR = 1.027; 95% CI, 0.798–1.321). Women with a prior medical history of cardiovascular disease treated with radiation therapy are at increased risk for an event and should be monitored for at least 6 months following treatment with radiation therapy.